TKJ and Graphic Design Training for Student Strengthening Facing UKK at SMK PGRI Amlapura - Putu Gde Sukarata; I Nyoman Gede Arya Astawa; Gusti Nyoman Ayu Sukerti; I Wayan Suasnawa; I Putu Bagus Arya Pradnaya (Dharma: Jurnal Pengabdian Masyarakat, 2023)
The Vocational High School of the Indonesian Teachers Association (SMK PGRI) Amlapura is a vocational school at the upper middle level that has four majors namely, hospitality, catering, computer network and multimedia engineering. Located in Amlapura City, Karangasem Regency, Bali Province. Based on the vocational education that is carried out, all students studying in vocational schools are required to take the expertise competency test (UKK) of each field that is in demand in accordance with the majors they choose. This UKK is carried out nationally and is a national practical test. This is what distinguishes an educational model that exists at the high school level. As for facing the National Practice Examination, schools generally provide assistance for their students.Bali State Polytechnic in this case implementing Tri Dharma Higher Education such as teaching, research and service. One of the Tri Dharma of the tertiary institution is the Commander of the Commander, where the community service aims to play a role and participate in building the welfare of the community. This service activity is carried out in accordance with existing academic culture.Bali State Polytechnic Department of Electrical Engineering Information Management Study Program is willing to accompany the students of SMK PGRI Amlapura in terms of preparing themselves to take part in UKK. This mentoring activity is a service activity. Assistance provided specifically to UKK Computer Network Engineering Program and UKK Multimedia Program. Activities in the form of exposure in theory and direct practice. The continuation of assistance is also done using WhatsApp Group media.